COMPARATIVE EFFICACY OF BACTERIAL VAGINOSIS LOCAL THERAPY IN PREGNANT WOMEN WITH OBESITY - I. O. Makarov; E. L. Borovkova (IRBIS LLC, 2016)
The article presents the results of comparative study of, dedicated to evaluation of clinical and laboratory efficacy of bacterial vaginosis local therapy in pregnant women with obesity.